Miniaturized shake-flask HPLC method for determination of distribution coefficient of drugs used in inflammatory bowel diseases - Brusač Edvin; Jeličić Mario-Livio; Klarić Daniela Amidžić; Mornar Ana (Acta Pharmaceutica)
A new method for determination of distribution coefficient of drugs azathioprine, 6-mercaptopurine and 6-thioguanine and nutrient folic acid used in the treatment of inflammatory bowel disease based on a miniaturized shake-flask and HPLC/DAD was developed. Special attention was made to the most commonly reported problems in the measurement of distribution coefficients using a shake-flask method such as mixing technique, speed and time, the temperature of experiment, type of buffer and its pH as well as n-octanol/buffer phase ratio. The concentration of compounds in the buffer is determined by HPLC directly from shake flasks or conventional 2-mL vials. The developed method was fully validated according to ICH guidelines. Furthermore, experimental data were successfully compared with lipophilicity and human intestinal absorption calculated by the use of four different theoretical approaches. The method shows potential for high-throughput measurements of a large number of compounds.